The State of General Education Schools in New Uzbekistan: Problems and Solutions - Nigora Sharopova; Zamir Jomurodov (Scientific Trends, 2025)
This article examines the current state and challenges of the general secondary education system in New Uzbekistan. Despite significant reforms aimed at improving the social status of teachers, updating curricula, and enhancing educational quality, persistent issues remain in infrastructure, teacher qualifications, and teaching methodologies. Key problems include outdated school facilities, insufficient professional development for educators, and curricula that do not fully foster critical thinking and practical skills. The article proposes comprehensive solutions such as modernizing infrastructure, reforming teacher training and certification systems, updating curricula to international standards, and improving assessment transparency. The successful implementation of these measures requires coordinated efforts from government bodies, educators, parents, and society at large. Ultimately, continuous investment and innovation in education are crucial for developing the potential of the younger generation and ensuring New Uzbekistan’s competitive position in the global educational landscape.
Keywords: General education schools, education quality, teacher qualifications, curricula, infrastructure, education reforms, New Uzbekistan, assessment system.